Examining the views of operating room nurses and physicians on the relationship between professional values and professional communication - Sedigheh Yeganeh; Camellia Torabizadeh; Tayebeh Bahmani; Zahra Molazem; Hamed Yeganeh Doust; Samira Daneshvar Dehnavi (BMC, 2022)
Abstract Purpose Professional communication and professional values are two basic concepts in operating rooms and should be studied more closely in view of the nature of work and the high circulation of patients in operating rooms. Methods The present work is a descriptive-analytic study with a cross-sectional design. The sample was 603 operating room physicians and personnel selected from the public hospitals of Shiraz. The data collection instruments were the 41-item professional communication questionnaire and the 26-item professional values scale. Results The results showed that the operating room nurses and physicians perceived the status of professional communication and professional values to be satisfactory. As for professional communication, the participants' perception of the domains of mutual respect and trust (p ≤ 0.001), teamwork (p ≤ 0.001), ethical competence (p ≤ 0.017), and workplace conflicts (p ≤ 0.001) was significant. As for professional values, only the dimension of care (p ≤ 0.016) was perceived to be significant. Moreover, a significant positive relationship was found to exist between professional communication and professional values (p ≤ 0.001). Conclusion Considering the significance of the concept of professional communication and its connection with professional values, it is recommended that operating room personnel and physicians receive systematic education about professional communication and the harms of destructive attitudes as part of their academic education and afterwards.